Preparation method of multi-coated lithium-rich manganese-based battery positive electrode material and positive electrode material

Through multiple cladding technology, lithium-rich manganese-based battery positive electrode material is prepared to form a composite cladding layer, which solves the problem of unstable performance of the material during circulation and significantly improves the cyclic stability and electrochemical performance of the material.

CN119143198BActive Publication Date: 2025-03-18PINGGAO GRP ENERGY STORAGE TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411598016.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-18
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

In practical applications, the existing lithium-rich manganese-based battery positive electrode materials have problems such as large irreversible capacity loss for the first time, unstable cycle performance, and serious voltage attenuation during charging and discharging, mainly due to its complex structure and phase change behavior, as well as the interface side reactions generated during the cycle.

Method used

Multiple coating technology is used to prepare lithium-rich manganese-based materials through sol-gel method and wet chemistry method to form a composite coating layer including TiO2, phosphate and other inorganic oxides, to improve the conductivity and ion transportability of the material and inhibit side reactions at the table interface.

Benefits of technology

Through multiple coating technology, the cyclic stability and electrochemical performance of the cathode material of lithium-rich manganese-based battery is significantly improved, the capacity loss and voltage attenuation are reduced, and the lithium ion transmission efficiency is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143198B_ABST
    Figure CN119143198B_ABST
Patent Text Reader

Abstract

The present invention relates to a preparation method and positive electrode material of a multi-coated lithium-rich manganese-based battery positive electrode material, belonging to the technical field of battery positive electrode materials. The present invention adopts a sol-gel method to prepare a lithium-rich manganese-based material, and adopts a wet chemical method to prepare a multi-coated lithium-rich manganese-based material: overcome the defects of the existing coated modified lithium-rich manganese-based positive electrode material in alleviating the dissolution of transition metals, inhibiting surface and interface side reactions, and improving the synergy of ion transmission performance, and provide a multi-coated lithium-rich manganese-based material and a preparation method composed of an inert oxide, a fast ion conductor, and a high-stability phosphate. The present invention inhibits the occurrence of surface and interface side reactions, reduces electrolyte decomposition, and enhances cycle stability, and the non-continuous island coating discontinuously forms a protective layer on the surface of the material, leaving many uncovered areas, which helps to maintain a high lithium ion transmission efficiency, thereby improving the charge and discharge performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery positive electrode materials, and in particular relates to a preparation method of a multi-coated lithium-rich manganese-based battery positive electrode material and a positive electrode material. Background Art

[0002] With the rapid development of electric vehicles and energy storage markets, the demand for lithium-ion batteries continues to increase. Traditional lithium-ion battery cathode materials (such as lithium cobalt oxide, lithium nickel cobalt manganese oxide, etc.) face many challenges in terms of cost, resource supply and environmental impact. Therefore, the development of new, high-performance and low-cost cathode materials has become a research hotspot.

[0003] Lithium-rich manganese-based cathode materials (xLi 2 MnO 3 ·(1-x)LiMO 2 , (M=Ni, Mn, Co, etc., 0.5≤x<1.0), LMR) is a new type of cathode material with high energy density and low cost, with high lithium content and unique structure, which can provide higher specific capacity (≥250mAh·g -1 ). As manganese is abundant in the earth's crust, inexpensive and environmentally friendly, lithium-rich manganese-based cathode materials have obvious advantages in terms of economy and sustainability. However, there are still some urgent problems to be solved in practical applications of lithium-rich manganese-based cathode materials, such as large irreversible capacity loss at the first time, unstable cycle performance, and severe voltage decay during charge and discharge. These problems are mainly attributed to their complex structure and phase change behavior, as well as the interfacial side reactions generated during the cycle process.

[0004] In order to solve the above problems of lithium-rich manganese-based cathode materials, coating modification technology has been widely studied and applied. By forming a protective layer on the surface of the material, it can effectively inhibit the surface and interface side reactions, stabilize the crystal structure of the material, and improve the cycle stability and electrochemical performance of the material. In recent years, research on the coating modification of lithium-rich manganese-based cathode materials has made significant progress. The most common coating materials are metal oxides, such as Al 2 O 3 、TiO 2 , MgO, etc. These coating materials are usually continuously attached to the surface of the positive electrode material particles, which improves the interface stability, inhibits the dissolution of transition metals, and thus improves the cycle stability. However, existing coating materials usually have poor conductivity and ion transport properties, which leads to a decrease in battery performance during the charge and discharge process, specifically manifested as capacity loss and reduced electrochemical performance.

[0005] Therefore, developing coating materials and coating methods with excellent conductivity and ion transport properties that can both protect the lithium-rich manganese-based positive electrode materials and maintain their high capacity and excellent electrochemical properties has become a technical problem that needs to be solved urgently. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a preparation method of a multi-coated lithium-rich manganese-based battery positive electrode material and a positive electrode material.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a multi-coated lithium-rich manganese-based battery positive electrode material, comprising the following steps:

[0008] S1. Preparation of lithium-rich manganese-based materials by sol-gel method:

[0009] S11, preparing an aqueous solution of lithium acetate, nickel acetate, and manganese acetate to form a metal salt solution, and preparing an aqueous solution of citric acid to form a citric acid solution;

[0010] S12, adding the citric acid solution dropwise into the metal salt solution, adjusting the pH to 7-9, stirring the whole process, heating and evaporating the solution to obtain a gel;

[0011] S13, vacuum drying the obtained gel, and calcining it in a muffle furnace after drying to obtain a lithium-rich manganese-based material;

[0012] S2. Preparation of multi-coated lithium-rich manganese-based materials using wet chemical method:

[0013] S21, dissolving phosphate in a small amount of deionized water, and then dropping the solution into anhydrous ethanol, mixing evenly to form a phosphate solution; dissolving a metal salt in a small amount of deionized water, and then dropping the solution into the phosphate solution, stirring and mixing evenly to obtain a phosphate mixed solution;

[0014] S22, adding the lithium-rich manganese-based material to the above phosphate mixed solution, heating and stirring continuously, adding ethanol after evaporation, stirring and mixing evenly, adding tetrabutyl titanate (Ti(OC 4 H 9 ) 4 ), and heated, and deionized water was added dropwise to promote Ti(OC 4 H 9 ) 4 Hydrolyze and wash several times with anhydrous ethanol to remove residues;

[0015] S23, vacuum drying the product obtained in step S22, grinding it, and calcining it in a muffle furnace to obtain a multi-coated lithium-rich manganese-based material.

[0016] Furthermore, in step S11, the amount of lithium acetate in the metal salt solution is 5% in excess to offset the evaporation loss of lithium during the calcination process; and the molar amount of citric acid is equal to the total molar amount of all metal ions in the metal salt solution.

[0017] Furthermore, in step S12, the heating temperature is 65-80°C.

[0018] Furthermore, in step S13, the vacuum drying temperature is 80-100°C, and the drying time is 18-30 hours.

[0019] Furthermore, in step S13, the calcination is a two-step calcination, the first step is a calcination temperature of 450-550°C, the time is 4-6 hours, and after the product is cooled, it is ground into a uniform powder; the second step is a calcination temperature of 800-950°C, the time is 10-15 hours, and after the product is cooled, it is ground into a fine powder with a mortar to obtain a lithium-rich manganese-based material.

[0020] Furthermore, in step S21, the phosphate is diammonium phosphate (NH 4 H 2 PO 4 ), diammonium hydrogen phosphate (NH 4 ) 2 HPO 4 ), ammonium phosphate (NH 4 ) 3 PO 4 );the phosphate is added in an amount according to which the product accounts for 1~4wt% of the lithium-rich manganese-based material; the metal salt is one or more of Al, Zr, and Mg soluble salts; the metal salt is added in an amount according to which the product accounts for 1~4wt% of the lithium-rich manganese-based material.

[0021] Further, in step S22, after the lithium-rich manganese-based material is added to the phosphate mixed solution, the temperature is set to 60-70°C and the stirring time is 3-6 hours.

[0022] Further, in step S22, the Ti(OC 4 H 9 ) 4 The amount is added according to the product accounting for 0.5~2wt% of the lithium-rich manganese-based material; adding Ti(OC 4 H 9 ) 4 Afterwards, the temperature was set to 40-60°C, the amount of deionized water was 0.25-1% of the volume of ethanol, and the rate of adding deionized water was 1-10s / drop interval.

[0023] Furthermore, in step S23, the vacuum drying temperature is 80-100°C, and the drying time is 18-30 hours; the calcination temperature is 400-600°C, and the calcination time is 4-8 hours.

[0024] Another object of the present invention is to provide a battery positive electrode material obtained by a preparation method of a multi-coated lithium-rich manganese-based battery positive electrode material.

[0025] Due to the adoption of the above technical scheme, it can be seen that (1) the present invention adopts the sol-gel method to prepare polycrystalline lithium-rich manganese-based materials. The materials generated by this method are mostly irregular polycrystalline with different grain boundaries and porosity. (2) The present invention adopts composite phosphate and metal salt for modification to construct a TiO 2 The key to this coating process is the introduction of phosphate and TiO 2 The coating layer is prepared by the synergistic reaction of residual alkali, phosphate and metal salt on the surface of the substrate material to prepare a lithium phosphate salt with high ion transfer efficiency. In addition, a highly stable metal oxide coating layer is prepared by combining the thermal decomposition reaction of the metal salt. Finally, a discontinuous TiO 2 The coating layer and the composite coating layer not only improve the electrochemical stability of the interface, but also enhance the performance of the overall battery by optimizing the lithium ion transmission channel. (3) In the hydrolysis process of tetrabutyl titanate of the present invention, the water content is controlled to be low, and water is added dropwise at a low speed to ensure that the hydrolysis reaction is uniform and controllable. The hydrolysis product directly formed in this process can be further heat treated to form TiO 2 The polycrystalline characteristics of the substrate material of the present invention determine its surface unevenness and porosity. The traditional continuous coating process is difficult to evenly distribute on such a substrate. Therefore, the present invention adopts a discontinuous island-shaped multiple coating technology, and hydrolyzes tetrabutyl titanate by adding water dropwise at a low speed to ensure that TiO 2 Able to form a uniform and effective coating layer on the polycrystalline surface, this method simplifies the process flow and significantly improves the electrochemical performance and cycle stability of the material.

[0026] In summary, the beneficial effects of the present invention are:

[0027] (1) Multiple protection effects: The present invention provides a multi-coated lithium-rich manganese-based material composed of an inert oxide, a fast ion conductor, and a high-stability phosphate. The fast ion conductor ensures that the material surface interface is resistant to Li + The transport properties of the electrolyte and the oxides can jointly inhibit the occurrence of surface and interface side reactions, reduce electrolyte decomposition, and enhance cycle stability.

[0028] (2) Higher ion transfer efficiency: The discontinuous island coating forms a protective layer on the surface of the material, leaving many uncovered areas, which helps maintain high lithium ion transfer efficiency and thus improves the battery’s charge and discharge performance.

[0029] (3) Flexible design and application: The design of multiple coating layers can be adjusted according to different battery design and application requirements, including the thickness, distribution and material type of the coating layer. This flexibility allows researchers to optimize the coating strategy to adapt to specific performance indicators and usage environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The present invention will be described in detail below with reference to the accompanying drawings and in combination with examples, and the advantages and implementation methods of the present invention will become more obvious. The contents shown in the accompanying drawings are only used to explain the present invention and do not constitute any limitation to the present invention in any sense. In the accompanying drawings:

[0031] Figure 1 X-ray diffraction patterns of lithium-rich manganese-based positive electrode materials prepared in Examples 1 to 3 of the present invention.

[0032] Figure 2 This is a scanning electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Example 1 of the present invention.

[0033] Figure 3 This is an energy dispersion spectrum surface scan energy spectrum of the lithium-rich manganese-based positive electrode material prepared in Example 1 of the present invention.

[0034] Figure 4 This is a scanning electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Example 2 of the present invention.

[0035] Figure 5 This is an energy dispersion spectrum surface scan energy spectrum of the lithium-rich manganese-based positive electrode material prepared in Example 2 of the present invention.

[0036] Figure 6 This is a scanning electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Example 3 of the present invention.

[0037] Figure 7 This is a transmission electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0038] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the best embodiment.

[0039] A method for preparing a multi-coated lithium-rich manganese-based battery positive electrode material comprises the following steps:

[0040] S1. Preparation of lithium-rich manganese-based materials by sol-gel method:

[0041] S11, preparing an aqueous solution of lithium acetate, nickel acetate, and manganese acetate to form a metal salt solution, and preparing an aqueous solution of citric acid to form a citric acid solution;

[0042] S12, adding the citric acid solution dropwise into the metal salt solution, adjusting the pH to 7-9, stirring the whole process, heating and evaporating the solution to obtain a gel;

[0043] S13, vacuum drying the obtained gel, and calcining it in a muffle furnace after drying to obtain a lithium-rich manganese-based material.

[0044] Wherein, in step S11, the amount of lithium acetate used is 5% in excess to offset the evaporation loss of lithium during the calcination process; the molar amount of citric acid is equal to the sum of the molar amounts of all metal ions in the metal salt solution.

[0045] Wherein, in step S12, the heating temperature is 65-80°C.

[0046] Wherein, in step S13, the vacuum drying temperature is 80-100°C, and the drying time is 18-30 hours.

[0047] Among them, in step S13, the calcination is a two-step calcination, the first step is a calcination temperature of 450~550℃, the time is 4~6h, and after the product is cooled, it is ground into a uniform powder; the second step is a calcination temperature of 800~950℃, the time is 10~15h, after the product is cooled, it is ground with a mortar to obtain a lithium-rich manganese-based material.

[0048] S2. Preparation of multi-coated lithium-rich manganese-based materials using wet chemical method:

[0049] S21, dissolving phosphate in a small amount of deionized water, and then dropping the solution into anhydrous ethanol, mixing evenly to form a phosphate solution; dissolving a metal salt in a small amount of deionized water, and then dropping the solution into the phosphate solution, stirring and mixing evenly to obtain a phosphate mixed solution;

[0050] S22, adding the lithium-rich manganese-based material to the above phosphate mixed solution, heating and stirring continuously, adding ethanol after evaporation, stirring and mixing evenly, adding tetrabutyl titanate (Ti(OC 4 H 9 ) 4 ), and heated, and deionized water was added dropwise to promote Ti(OC 4 H 9 ) 4 Hydrolyze and wash several times with anhydrous ethanol to remove residues.

[0051] S23, vacuum drying the product obtained in step S22, grinding it, and calcining it in a muffle furnace to obtain a multi-coated lithium-rich manganese-based material.

[0052] Wherein, in step S21, the phosphate is diammonium phosphate (NH 4 H 2 PO 4 ), diammonium hydrogen phosphate (NH 4 ) 2 HPO 4 ), ammonium phosphate (NH 4 ) 3 PO 4 );the phosphate is added in an amount according to which the product accounts for 1~4wt% of the lithium-rich manganese-based material; the metal salt is one or more soluble salts of Al, Zr, and Mg; the metal salt is added in an amount according to which the product accounts for 1~4wt% of the lithium-rich manganese-based material.

[0053] Wherein, in step S22, after the lithium-rich manganese-based material is added to the phosphate mixed solution, the temperature is set to 60-70°C and the stirring time is 3-6 hours.

[0054] Wherein, in step S22, the Ti(OC 4 H 9 ) 4 The amount is added according to the product accounting for 0.5~2wt% of the lithium-rich manganese-based material; adding Ti(OC 4 H 9 ) 4 Afterwards, the temperature was set to 40-60°C, the amount of deionized water was 0.25-1% of the volume of ethanol, and the rate of adding deionized water was 1-10s / drop interval.

[0055] Wherein, in step S23, the vacuum drying temperature is 80-100°C, and the drying time is 18-30 hours; the calcination temperature is 400-600°C, and the calcination time is 4-8 hours.

[0056] Another object of the present invention is to provide a battery positive electrode material obtained by a preparation method of a multi-coated lithium-rich manganese-based battery positive electrode material.

[0057] Embodiment 1:

[0058] A method for preparing a multi-coated lithium-rich manganese-based battery positive electrode material comprises the following steps:

[0059] S1. Preparation of lithium-rich manganese-based materials Li by sol-gel method 1.2 Mn 0.6 Ni 0.2 O 2 :

[0060] S11, dissolving manganese acetate, nickel acetate and lithium acetate in a stoichiometric ratio in deionized water, wherein the lithium acetate is in excess of 5% to offset the evaporation loss of lithium during the calcination process, to form a green metal salt solution after dissolution; dissolving citric acid in deionized water to form a citric acid solution, the molar amount of which is equal to the sum of the molar amounts of all metal ions in the metal salt solution;

[0061] S12, adding the citric acid solution dropwise into the metal salt solution while stirring the solution. After the mixture is evenly mixed, adding ammonia water to adjust the pH value of the mixture to about 8, and evaporating the mixture at 70° C. while stirring rapidly to generate a green gel.

[0062] S13, the obtained green gel was transferred to a crucible while hot, dried in a vacuum oven at 80°C for 24h, and then calcined in a muffle furnace at 500°C for 5h. After the calcined product was cooled, it was ground into a uniform powder, and then calcined at 900°C for 12h. After the calcined product was cooled, it was ground into powder with a mortar to obtain a lithium-rich manganese-based material Li 1.2 Mn 0.6 Ni 0.2 O 2 .

[0063] S2. Preparation of TiO by wet chemical method 2 -Lithium aluminum phosphate coated Li 1.2 Mn 0.6 Ni 0.2 O 2 Material:

[0064] S21, according to 2wt% addition amount, NH 4 H 2 PO 4 Dissolve in 10 mL of deionized water, then drop into 30 mL of anhydrous ethanol and mix well to form a phosphate solution; add Al(NO 3 ) 3 Dissolve in 10 mL of deionized water, then dropwise add to the above phosphate solution, continue stirring and mixing to obtain a phosphate mixed solution;

[0065] S22, lithium-rich manganese-based material Li 1.2 Mn 0.6 Ni 0.2 O 2 Add to the above phosphate mixed solution, heat to 60℃ and stir continuously for 5h, evaporate to dryness, add 50mL ethanol, stir and mix evenly, add Ti(OC 4 H 9 ) 4 , and heated at 45°C, 0.25 mL of deionized water was added dropwise at an interval of 5 s / drop to promote Ti(OC 4 H9 ) 4 After hydrolysis, the samples were washed several times with anhydrous ethanol to remove any residues.

[0066] S23, the product obtained in step S22 was dried under vacuum at 80°C for 24h, ground and calcined in a muffle furnace at 500°C for 6h to obtain a discontinuous TiO 2 -Lithium aluminum phosphate coated Li 1.2 Mn 0.6 Ni 0.2 O 2 (1wt%TiO 2 -1wt% lithium aluminum phosphate) material.

[0067] like Figure 1 As shown, the TiO 2 -Lithium aluminum phosphate coated Li 1.2 Mn 0.6 Ni 0.2 O 2 The materials were characterized by X-ray diffraction (XRD). It can be seen from the figure that the crystal structure of all samples is marked as α-NaFeO 2 The layered structure (R3m space group) is consistent with the structure of most lithium-rich materials reported in the literature. The (006) / (102) and (018) / (110) peaks are clearly split, indicating that the layered structure of the synthesized material has a high degree of crystallinity.

[0068] like Figure 2 and Figure 3 As shown, the TiO 2 -Lithium aluminum phosphate coated Li 1.2 Mn 0.6 Ni 0.2 O 2 The materials were characterized by scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). The results showed that the grain size of the surface-modified samples did not change significantly, discontinuously coated materials appeared on the surface of the particles, and Al, P, and Ti elements were distributed on the surface.

[0069] Electrochemical performance characterization:

[0070] Electrode preparation: Mix the prepared lithium-rich manganese-based material with acetylene black and polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, and grind them in a mortar. Then add an appropriate amount of solvent N-methylpyrrolidone (NMP) and grind them again to dissolve and make them fluid. Spread the mixed slurry evenly on aluminum foil, place it in a vacuum drying oven, dry it at 80°C for 12 hours, and use a manual press to cut out the positive electrode sheet of the required size.

[0071] Battery assembly: lithium metal sheet as negative electrode, Celgard 2500 as separator, 1M LiPF 6 Dissolved in a 1:1 volume ratio EC / DMC mixed solution as the electrolyte. Place the lithium sheet, separator, electrolyte, and positive electrode sheet into the negative electrode shell in sequence, drip the electrolyte to ensure that the electrode sheet and separator are completely wetted, cover the positive electrode shell, and seal the battery with a sealing machine to obtain a CR2025 button battery.

[0072] Electrochemical performance test: constant current charge and discharge mode, 1C=250mA·g -1 . All batteries need to be left to stand for 24 hours before testing to ensure that the electrolyte fully infiltrates the diaphragm. During the test, the battery was placed in a 30°C constant temperature box and fully activated at a voltage range of 2.0-4.8V at a rate of 0.1C for the first three weeks, and then tested at a rate of 1C at a voltage range of 2.0-4.6V. The electrochemical impedance spectroscopy (EIS) test frequency was 100kHz to 0.01Hz, with an amplitude of 5mV.

[0073] The TiO obtained in Example 1 2 -Lithium aluminum phosphate coated Li 1.2 Mn 0.6 Ni 0.2 O 2 The electrochemical performance of the material was characterized in the above manner. As can be seen from Table 1, at a rate of 0.1C, the first-week capacity was 265.3 mAh g -1 At 1C rate, the capacity is 226.5 mAh g -1 After 100 cycles, the capacity retention rate was 88.7% and the voltage drop was 0.189V. The coating material improved the cycle stability of the lithium-rich material and reduced the voltage drop. The electrochemical kinetic behavior of the electrode was studied by electrochemical impedance spectroscopy (EIS) testing, which usually shows a straight line in the low-frequency region and a semicircle with a small intercept in the high-frequency region. Among them: the small intercept corresponds to the electrolyte resistance (Rs), the high-frequency semicircle radius is related to the charge transfer resistance (Rct), and the low-frequency straight line is attributed to the Li in the electrode material. + Diffusion. The resulting TiO 2 -Lithium aluminum phosphate coated Li 1.2 Mn 0.6 Ni 0.2 O 2 The Rct of the material after 100 cycles is 63.17Ω, which shows that the TiO prepared by the method of Example 1 2 -Lithium aluminum phosphate coated Li 1.2 Mn 0.6 Ni 0.2 O 2 The material, the coating layer is a fast ion conductor, which can reduce the surface interface impedance.

[0074] Embodiment 2:

[0075] A method for preparing a multi-coated lithium-rich manganese-based battery positive electrode material comprises the following steps:

[0076] S1. Preparation of lithium-rich manganese-based materials Li by sol-gel method 1.2 Mn 0.6 Ni 0.2 O 2 :

[0077] S11, dissolving manganese acetate, nickel acetate and lithium acetate in a stoichiometric ratio in deionized water, wherein the lithium acetate is in excess of 5% to offset the evaporation loss of lithium during the calcination process, to form a green metal salt solution after dissolution; dissolving citric acid in deionized water to form a citric acid solution, the molar amount of which is equal to the sum of the molar amounts of all metal ions in the metal salt solution;

[0078] S12, adding the citric acid solution dropwise into the metal salt solution while stirring the solution. After the mixture is evenly mixed, adding ammonia water to adjust the pH value of the mixture to about 8, and evaporating the mixture at 70° C. while stirring rapidly to generate a green gel.

[0079] S13, the obtained green gel was transferred to a crucible while hot, dried in a vacuum oven at 80°C for 24h, and then calcined in a muffle furnace at 500°C for 5h. After the calcined product was cooled, it was ground into a uniform powder, and then calcined at 900°C for 12h. After the calcined product was cooled, it was ground into powder with a mortar to obtain a lithium-rich manganese-based material Li 1.2 Mn 0.6 Ni 0.2 O 2 .

[0080] S2. Preparation of TiO by wet chemical method 2 -Lithium zirconium phosphate-zirconia coated Li 1.2 Mn 0.6 Ni 0.2 O 2 Material:

[0081] S21, according to 2wt% addition amount, NH 4 H 2 PO 4 Dissolve in 10 mL of deionized water, then drop into 30 mL of anhydrous ethanol and mix well to form a phosphate solution; add Zr(NO 3 ) 4 Dissolve in 10 mL of deionized water, then dropwise add to the above phosphate solution, continue stirring and mixing to obtain a phosphate mixed solution;

[0082] S22, lithium-rich manganese-based material Li1.2 Mn 0.6 Ni 0.2 O 2 Add to the above phosphate mixed solution, heat to 65℃ and stir continuously for 4h, evaporate to dryness, add 50mL ethanol, stir and mix evenly, add Ti(OC 4 H 9 ) 4 , and heated at 50°C, 0.25 mL of deionized water was added dropwise at an interval of 7 seconds per drop, to promote Ti(OC 4 H 9 ) 4 After hydrolysis, the samples were washed several times with anhydrous ethanol to remove any residues.

[0083] S23, the product obtained in step S22 was dried under vacuum at 80°C for 24h, ground and calcined in a muffle furnace at 550°C for 5h to obtain a discontinuous TiO 2 -Lithium zirconium phosphate-zirconia coated Li 1.2 Mn 0.6 Ni 0.2 O 2 (1wt%TiO 2 -1wt% lithium zirconium phosphate -0.5wt% zirconium oxide) material.

[0084] like Figure 1 As shown, the TiO obtained in Example 2 2 -Lithium zirconium phosphate-zirconia coated Li 1.2 Mn 0.6 Ni 0.2 O 2 The materials were characterized by X-ray diffraction (XRD). It can be seen from the figure that the crystal structure of all samples is marked as α-NaFeO 2 The layered structure (R3m space group) and the (006) / (102) and (018) / (110) peaks show obvious splitting, indicating that the layered structure of the synthesized material has a high degree of crystallinity.

[0085] like Figure 4 and Figure 5 As shown, the TiO obtained in Example 2 2 -Lithium zirconium phosphate-zirconia coated Li 1.2 Mn 0.6 Ni 0.2 O 2 The materials were characterized by scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). The results showed that the grain size of the surface-modified samples did not change significantly, discontinuously coated materials appeared on the surface of the particles, and Zr, P, and Ti elements were distributed on the surface.

[0086] The electrochemical performance of the material obtained in Example 2 was characterized by the method in Example 1. As can be seen from Table 1, at a rate of 0.1C, the first cycle capacity was 263.5 mAh·g -1 At 1C rate, the capacity is 231.4 mAh g -1 After 100 cycles, the capacity retention rate is 91.3% and the voltage drop is 0.178V. Due to the large amount of added Zr, additional ZrO 2 The coating layer further improves the cycle stability of lithium-rich materials. EIS test shows that the obtained TiO 2 -Lithium zirconium phosphate-zirconia coated Li 1.2 Mn 0.6 Ni 0.2 O 2 After 100 cycles, the Rct of the material is 53.68Ω. 2 -Lithium zirconium phosphate-zirconia coated Li 1.2 Mn 0.6 Ni 0.2 O 2 Materials can reduce impedance to a greater extent.

[0087] Embodiment 3:

[0088] A method for preparing a multi-coated lithium-rich manganese-based battery positive electrode material comprises the following steps:

[0089] S1. Preparation of lithium-rich manganese-based materials Li by sol-gel method 1.2 Mn 0.6 Ni 0.2 O 2 :

[0090] S11, dissolving manganese acetate, nickel acetate and lithium acetate in a stoichiometric ratio in deionized water, wherein the lithium acetate is in excess of 5% to offset the evaporation loss of lithium during the calcination process, to form a green metal salt solution after dissolution; dissolving citric acid in deionized water to form a citric acid solution, the molar amount of which is equal to the sum of the molar amounts of all metal ions in the metal salt solution;

[0091] S12, adding the citric acid solution dropwise into the metal salt solution while stirring the solution. After the mixture is evenly mixed, adding ammonia water to adjust the pH value of the mixture to about 8, and evaporating the mixture at 70° C. while stirring rapidly to generate a green gel.

[0092] S13, the obtained green gel was transferred to a crucible while hot, dried in a vacuum oven at 80°C for 24h, and then calcined in a muffle furnace at 500°C for 5h. After the calcined product was cooled, it was ground into a uniform powder, and then calcined at 900°C for 12h. After the calcined product was cooled, it was ground into powder with a mortar to obtain a lithium-rich manganese-based material Li1.2 Mn 0.6 Ni 0.2 O 2 .

[0093] S2. Preparation of TiO by wet chemical method 2 -Li-MgPO4 coated Li 1.2 Mn 0.6 Ni 0.2 O 2 Material:

[0094] S21, according to 2wt% addition amount, NH 4 H 2 PO 4 Dissolve in 10 mL of deionized water, then add dropwise to 30 mL of anhydrous ethanol and mix well to form a phosphate solution; add Mg(NO 3 ) 2 6H 2 O is dissolved in 10 mL of deionized water, and then added dropwise to the above phosphate solution, and stirred continuously to mix evenly to obtain a phosphate mixed solution;

[0095] S22, lithium-rich manganese-based material Li 1.2 Mn 0.6 Ni 0.2 O 2 Add to the above phosphate mixed solution, heat to 60℃ and stir continuously for 5h, evaporate to dryness, add 50mL ethanol, stir and mix evenly, add Ti(OC 4 H 9 ) 4 , and heated at 45°C, 0.5 mL of deionized water was added dropwise at an interval of 2 seconds per drop, to promote Ti(OC 4 H 9 ) 4 After hydrolysis, the samples were washed several times with anhydrous ethanol to remove any residues.

[0096] S23, the product obtained in step S22 was dried under vacuum at 80°C for 24h, ground and calcined in a muffle furnace at 500°C for 6h to obtain a discontinuous TiO 2 -Li-MgPO4 coated Li 1.2 Mn 0.6 Ni 0.2 O 2 (2wt%TiO 2 -2wt% lithium magnesium phosphate) material.

[0097] like Figure 1 As shown, the TiO obtained in Example 3 2 -Li-MgPO4 coated Li 1.2 Mn0.6 Ni 0.2 O 2 The materials were characterized by X-ray diffraction (XRD). It can be seen from the figure that the crystal structure of all samples is marked as α-NaFeO 2 The layered structure (R3m space group) and the (006) / (102) and (018) / (110) peaks show obvious splitting, indicating that the layered structure of the synthesized material has a high degree of crystallinity.

[0098] like Figure 6 As shown, the TiO obtained in Example 3 2 -Li-MgPO4 coated Li 1.2 Mn 0.6 Ni 0.2 O 2 The material was characterized by scanning electron microscopy (SEM), and the results showed that a discontinuous island coating was formed on the surface of the material. Figure 7 As shown, the transmission electron microscopy (TEM) characterization results show that a coating layer with a thickness of about 3 nm is formed on the surface.

[0099] The method in Example 1 was used to treat the TiO 2 -Li-MgPO4 coated Li 1.2 Mn 0.6 Ni 0.2 O 2 The electrochemical performance of the material was characterized. As can be seen from Table 1, at a rate of 0.1C, the first-week capacity was 264.7 mAh g -1 At 1C rate, the capacity is 230.8 mAh g -1 The capacity retention rate is 90.6% and the voltage drop is 0.192V. The cycle stability of the lithium-rich material is significantly improved and the voltage drop is reduced after coating. EIS test shows that the obtained TiO 2 -Li-MgPO4 coated Li 1.2 Mn 0.6 Ni 0.2 O 2 After 100 cycles, the Rct of the material is 69.85Ω. 2 -Li-MgPO4 coated Li 1.2 Mn 0.6 Ni 0.2 O 2 Materials can reduce impedance, but if added in large quantities, the surface coverage of discontinuous islands will increase. This inactive substance will reduce electronic conductivity and ion transmission rate.

[0100] Comparative Example 1:

[0101] The lithium-rich manganese-based material Li was prepared by a method similar to that in Example 1.1.2 Mn 0.6 Ni 0.2 O 2 The electrochemical performance test was carried out. From Table 1, it can be seen that at a rate of 0.1C, the first week capacity is 268.2 mAh g -1 At 1C rate, the capacity is 207.1 mAh g -1 , the capacity retention rate is 80.3%, the voltage drop is 0.232V, and the Rct is 95.32Ω after 100 cycles.

[0102] Comparative Example 2:

[0103] S1. Prepare lithium-rich manganese-based material Li by the method of Example 1 1.2 Mn 0.6 Ni 0.2 O 2 .

[0104] S2. Preparation of discontinuous TiO 2 -Lithium aluminum phosphate coated Li 1.2 Mn 0.6 Ni 0.2 O 2 Material:

[0105] S21, according to 10wt% addition amount, NH 4 H 2 PO 4 Dissolve in 10 mL of deionized water, then drop into 30 mL of anhydrous ethanol and mix well to form a phosphate solution; add Al(NO 3 ) 3 Dissolve in 10 mL of deionized water, then dropwise add to the above phosphate solution, continue stirring and mixing to obtain a phosphate mixed solution;

[0106] S22, lithium-rich manganese-based material Li 1.2 Mn 0.6 Ni 0.2 O 2 Add to the above phosphate mixed solution, heat to 60℃ and stir continuously for 5h, evaporate to dryness, add 50mL ethanol, stir and mix evenly, add Ti(OC 4 H 9 ) 4 , and heated at 45°C, 2 mL of deionized water was added dropwise at an interval of 1 s / drop to promote Ti(OC 4 H 9 ) 4 After hydrolysis, the samples were washed several times with anhydrous ethanol to remove any residues.

[0107] S23, the product obtained in step S22 was dried under vacuum at 80°C for 24h, ground and calcined in a muffle furnace at 500°C for 6h to obtain a discontinuous TiO 2 -Lithium aluminum phosphate coated Li 1.2 Mn 0.6 Ni 0.2 O 2 (3wt%TiO 2 -5wt% lithium aluminum phosphate) material.

[0108] The electrochemical performance of Comparative Example 2 was tested. It can be seen from Table 1 that at a rate of 0.1C, the first-week capacity was 257.1 mAh g -1 At 1C rate, the capacity is 190.7 mAh g -1 , the capacity retention rate is 77.2%, the voltage drop is 0.258V, and the Rct is 108.38Ω after 100 cycles. It can be seen that too high a coating amount will deteriorate the material performance.

[0109] The comparison of electrochemical performances of batteries assembled with the materials prepared in Examples 1 to 3, Comparative Examples 1 and 2 is shown in Table 1.

[0110] Table 1 Electrochemical performance data of batteries assembled from materials prepared in Examples 1 to 3, Comparative Examples 1 and 2

[0111]

[0112] The embodiments of the present invention are described in detail above, but the contents are only preferred embodiments of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.

Claims

1. A method for preparing a multi-coated lithium-rich manganese-based battery positive electrode material, characterized in that: The following steps are involved: S1. Preparation of lithium-rich manganese-based materials by sol-gel method: S11, preparing an aqueous solution of lithium acetate, nickel acetate, and manganese acetate to form a metal salt solution, and preparing an aqueous solution of citric acid to form a citric acid solution; the amount of lithium acetate used is 5% in excess; S12, adding the citric acid solution dropwise into the metal salt solution, adjusting the pH to 7-9, stirring the whole process, heating and evaporating the solution to obtain a gel; S13, vacuum drying the obtained gel, and calcining it in a muffle furnace after drying to obtain a lithium-rich manganese-based material; S2. Preparation of multi-coated lithium-rich manganese-based materials using wet chemical method: S21, dissolving phosphate in deionized water, and then dropping it into anhydrous ethanol, mixing evenly to form a phosphate solution; dissolving a metal salt in a small amount of deionized water, wherein the metal salt is one or more soluble salts of Al, Zr, and Mg, and then dropping it into the phosphate solution, continuously stirring and mixing evenly to obtain a phosphate mixed solution; S22, adding the lithium-rich manganese-based material to the phosphate mixed solution, heating and continuously stirring, adding ethanol after evaporation, stirring and mixing evenly, adding Ti(OC4H9)4, and heating, adding deionized water dropwise to promote the hydrolysis of Ti(OC4H9)4, and washing with anhydrous ethanol; S23, vacuum drying the product obtained in step S22, grinding it and calcining it in a muffle furnace to obtain a multi-coated lithium-rich manganese-based material; In step S22, after adding Ti(OC4H9)4, the temperature is set to 40-60°C, the amount of deionized water is 0.25-1% of the volume of ethanol, and the rate of adding deionized water is 1-10s / drop interval.

2. The method for preparing a multi-coated lithium-rich manganese-based battery positive electrode material according to claim 1, characterized in that: In step S11, the molar amount of the citric acid is equal to the total molar amount of all metal ions in the metal salt solution.

3. The method for preparing a multi-coated lithium-rich manganese-based battery positive electrode material according to claim 1, characterized in that: In step S12, the heating temperature is 65-80°C.

4. The method for preparing a multi-coated lithium-rich manganese-based battery positive electrode material according to claim 1, characterized in that: In step S13, the vacuum drying temperature is 80-100°C, and the drying time is 18-30 hours.

5. The method for preparing a multi-coated lithium-rich manganese-based battery positive electrode material according to claim 1, characterized in that: In step S13, the calcination is a two-step calcination. The first step is performed at a calcination temperature of 450-550°C for 4-6 hours. After the product is cooled, it is ground into a uniform powder. The second step is performed at a calcination temperature of 800-950°C for 10-15 hours. After the product is cooled, it is ground into a fine powder with a mortar to obtain a lithium-rich manganese-based material.

6. The method for preparing a multi-coated lithium-rich manganese-based battery positive electrode material according to claim 1, characterized in that: In step S21, the phosphate is one or more of NH4H2PO4, (NH4)2HPO4, and (NH4)3PO4.

7. The method for preparing a multi-coated lithium-rich manganese-based battery positive electrode material according to claim 1, characterized in that: In step S22, after the lithium-rich manganese-based material is added to the phosphate mixed solution, the temperature is set to 60-70°C and the stirring time is 3-6 hours.

8. The method for preparing a multi-coated lithium-rich manganese-based battery positive electrode material according to claim 1, characterized in that: In step S23, the vacuum drying temperature is 80-100°C, and the drying time is 18-30 hours; the calcination temperature is 400-600°C, and the calcination time is 4-8 hours.

9. A multi-coated lithium-rich manganese-based battery positive electrode material, characterized in that: The positive electrode material is prepared by the method for preparing the multi-coated lithium-rich manganese-based battery positive electrode material according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Lithium-rich manganese-based composite positive electrode material and preparation method thereof

    CN107910542A

  • Preparation method of ultrahigh-capacity ternary lithium-rich manganese-based composite electrode material

    CN112635725A